(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Ginger (Zingiber officinale Roscoe), a famous herbaceous plant, has been widely used as a flavoring agent and natural remedy for centuries. Furthermore, the consumption of ginger rhizome is a standard conventional treatment to relieve common health problems, including pain, nausea, and vomiting. Ginger is quite popular because of an oily component called gingerol, which gives it its particular sharp and hot flavor. Ginger Anti-Inflammatory Massage Oil will specifically benefit those who commonly experience body pain, cramps, and inflammation. Table 10 shows the result of the t-test to see if there is a significant difference in the assessment of evaluated factors between the two groups of massage therapists (M.T.) and chemical engineers (C.E.). For both groups, the overall weighted mean and variance are supplied, as is the t-critical value with a significance level of 0.5 and degrees of freedom of 8. Is 2.306. For the comparison of the two groups, the computed t-value is 2.547, and the corresponding p-value is 2.547. Based on these findings, the null hypothesis is accepted, indicating that there is no significant difference in the assessment of the examined variables between the two groups. As a result, the answer is that there is a substantial difference in the ratings of the two groups of respondents in terms of the ingredients, procedure, effectiveness, healing duration, and presentation. For further enhancement and improvement of the project, the ensuing discussion and the recommendation proposed are as follows: Regarding ingredients, two of the respondents suggested using an alternative oil other than olive oil to lower the price. In terms of procedures, one respondent suggested letting the oil soak for at least 10 minutes. In terms of effectiveness, two of the respondents suggested adding eucalyptus oil and/or methanol crystal for a cooling effect. In terms of healing duration, one of the respondents suggested adding other sources of fragrance; in terms of presentation, one of the respondents suggested storing the product in a dropper (serum-like) packaging for much more convenient use.